ANALISIS MISKONSEPSI PESERTA DIDIK SMP IT AL FAHMI PADA MATA PELAJARAN IPA - Arda Arda; Anita Anita (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2021)
This research aims to determine the misconception of students at SMP IT Al Fahmi on the concept of motion. This research is descriptive quantitative with survey method. Data collection was carried out through written test using multiple choice questions equipped with Certainty of Response Index (CRI). The data analysis show that conception achievement on the concept of motion was 50.95% knowing the concept, 23.81% missing the concept and 25.24% not knowing the concept. Misconceptions occur in all concepts of motion, all straight motion (31.75%), force (20.24%) and Newton's law (20.63%). Many students misconceptions occur in the questions indicators determining displacement, resultant force, action and reaction force.